Evaluation of Quality Costs in the Production Organization - Pristavka, Miroslav; Kristof, Koloman (Manufacturing Technology Journal, 2018)
Within the context and term of quality it can be comprehended as a subjective character. Every individual has its own requirements, expectations or standards on specific product or service. Thus, these parameters are then connected and defined by different priorities. Many of the customers are willing to pay more money for increased quality of bought product however many of them are forced to decrease their requirements due to the costs and they have to be satisfied by products with lower quality or lesser amount of defined parameters. The main aim of the paper is to observe and analysis of cost system and its effect on product quality through the monitoring, analysis and evaluation of production costs in selected organization. Due to the comprehensive evaluation of the effects of investments on the resulting quality in selected organization a various methods was employed. Among used methods was comparison of investments into production quality by data analysis according to PAF model, mathematics and statistical parameters and Pareto's analysis. There were suggested individual steps by utilization which allows determining, evaluating and creating an individual system of observation and evaluation. Such a system of costs analysis is then suitable for selected companybut not limited to it. The utilization of such a system is therefore applicable at any company or organization which is focused on custom small-series production.
Keywords: quality; quality control; costs on quality; PAF model; Pareto's analysis